(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article is devoted to the study of cryptocurrencies as an innovative tool of the modern financial system, their role in the transformation of traditional financial processes, as well as the analysis of risks and opportunities associated with their use. The paper examines the key characteristics of cryptocurrencies, their economic importance, as well as examples of the integration of digital assets into national economies. Important attention is paid to the issues of regulation, security and stability of the cryptocurrency markets.